Utilização de procedimentos multivariados no consumo de água e energia elétrica em habitações sociais com sistema de aquecimento solar - Tutia, Marcelo Hiroshi [UNESP] (2015)
Nowadays, renewable energy sources are exploited and used for the development of society and stand out for being cleaner and less polluting than non-renewable energy sources. These renewable energy sources, solar energy is one of the most exploited, used in photovoltaic systems for power generation and solar water heating systems, the second use cited the best-known and can be seen in homes, businesses and industries. The solar heating system has among its objectives, to provide energy saving because it provides hot water without the need for electrical systems, such as electric shower, which is one of the devices that consume more energy. To provide economy of energy consumption, minimize environmental impacts, redirect investments in new sources of electricity, the Government of the State of São Paulo, together with the Development Company Housing and Urban State of São Paulo - CDHU, as housing policy, installed in homes of social interest built from 2007, the solar heating system water. In Ourinhos - SP, Helena Braz Vendramini housing project was awarded the solar heating system water in homes, but in the same city, there is another housing project, the Orlando Quagliato, but being older, does not have the solar heating system, a factor that motivated this study and the search for determinants for the viability and recommendation of key features to optimize the alternative energy source to use. The objective of this research was to apply procedures and techniques of multivariate analysis in evaluating the economic impact and the pursuit of fundamental socioeconomic identifiers for the description of a rational use of water policy and energy in housing with and without solar water heating system. The results showed that differences between the housing are observed for combinations of consumption and socioeconomic variables and the association of positivity between these sets of variables was...